Failure evidences of reduced span bridges in case of extreme rainfalls - The case of Livorno - Mario Lucio Puppio; Sara Novelli; Mauro Sassu (Fracture and Structural Integrity)
The heavy rainfalls occurring in Italy in the last few years focused the attention on the vulnerability of the land and the related infrastructures. Critical situations involving losses of human life and deterioration or failure of relevant structures are frequent. These events were due to: (1) improper land-use; (2) aging of infrastructures, (3) insufficient maintenance and protection; (4) climate changes causing rainstorms similar to tropical events. The failure of small bridges in road networks plays a key role in this sense. The present paper aims to analyse the behaviour of small bridges during rainfalls or floods. In particular, the recent case of Livorno is analysed. The Italian territory has about 460.000 small bridges, mostly designed without the support of technical codes or a proper interaction between the hydraulic and structural aspects. A large part of them can be submerged by water flows during rainfalls and pushed by unexpected actions. The failure scenarios allow identifying the hydraulic and structural vulnerabilities through a specific survey. A classification of small bridges on the basis of submergibility indexes is eventually proposed